The Influence of Online Customer Reviews and Content Marketing on Scarlett Whitening's Purchase Decision on Tiktok Users in Makassar City - Mega Yuliarsih, Mega Yuliarsih; Haedar Akib; Yusi Irensi Seppa; Siti Syarifah Wafiqah Wardah; Alifia Ainun Rizky (Business Research and Administration Innovation, 2025)
The Influence of Online Customer Reviews and Content Marketing on  Scarlett Whitening's Purchase Decisions on Tiktok Users in Makassar City. This study aims to find out how the Influence of Online Customer Reviews  and Content Marketing on Purchase Decisions both Simultaneously and Partially where Scarlett Users and Tiktok Marketplace are the object of research. This research uses Quantitative research type. The data collection technique used is through primary data (questionnaires and observations). The sampling technique uses Purposive Sampling technique with data collection using questionnaires. The data obtained were processed using SPSS 22 which consisted of multiple regression analysis which was first tested using validity tests, reliability tests, and normality tests. The results showed that the Online Customer Review variable had a significant effect on purchasing decisions with a T count of 6,658 > T   table  1.984 with a significance value of 0.000 < 0.05, Content Marketing had a significant effect on purchasing decisions with a calculated T value of 8,252 > T table  1.984 with a significance value of 0.000 < 0.05 and there is a simultaneous influence of online customer review and content marketing on the  purchase decision of Scarlett Whitening on TikTok users in Makassar City with acalculated F value of  42,573 > 3.09 Ftable. The value of the Coefficient of Determination (Adjusted R2) obtained is 0.570, this means that purchasing decisions are  influenced by online customer reviews and content marketing as  much as 57%, while the rest is influenced by other factors.